2015
DOI: 10.1063/1.4928287
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of Ag/ZnO core/shell nanostructures prepared by excimer laser ablation in liquid

Abstract: Ag/ZnO core/shell nanostructure was synthesised by a 248-nm KrF excimer pulsed laser ablation in a liquid solution for the first time. It was found that the surface plasma resonance absorption of the Ag/ZnO core/shell nanostructures can be tuned by the thickness of the ZnO shell, which is in agreement with the finite difference in the time domain simulation. Furthermore, the ultraviolet emission spectrum of the Ag/ZnO core/shell nanostructures was stronger and blue-shifted compared with that of pure ZnO nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Singh and Soni found that increasing the irradiation period of Ag and Al NPs in water caused the particles first to evolve into a network-type structure, then into core–shell structures, and finally into rattle-type Ag@Al 2 O 3 because of the Kirkendall effect . Varying the ablation period of gold or zinc targets in LAL-synthesized Ag colloids allowed the modulation of the Au or ZnO shell thickness of the resultant Ag@Au , and Ag@ZnO core–shell structures, respectively. Nevertheless, most studies on the processing time during LAL either focus on the concentration or supersaturation effects in batch reactors or trigger LFL processes that are naturally more pronounced at elevated concentrations.…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh and Soni found that increasing the irradiation period of Ag and Al NPs in water caused the particles first to evolve into a network-type structure, then into core–shell structures, and finally into rattle-type Ag@Al 2 O 3 because of the Kirkendall effect . Varying the ablation period of gold or zinc targets in LAL-synthesized Ag colloids allowed the modulation of the Au or ZnO shell thickness of the resultant Ag@Au , and Ag@ZnO core–shell structures, respectively. Nevertheless, most studies on the processing time during LAL either focus on the concentration or supersaturation effects in batch reactors or trigger LFL processes that are naturally more pronounced at elevated concentrations.…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
“…Particles generated by LSPC, and especially LAL (elemental, alloy, and oxide particles), are also good candidates for the synthesis of hybrid composites. This method is termed two-step or consecutive LAL (laser ablation of another material inside the former LAL-synthesized colloidal solution) and has enabled the fabrication of doped/core–shell nanocomposites (e.g., Pt–TiO 2 , Ag–TiO 2 , Au–Si, Ag@ZnO, Al 2 O 3 @Ag, Al 2 O 3 @AgAu, and Ag@Au). These two-step LAL-generated composites can be further used as colloidal additives for the in situ conjugation synthesis of trimetallic composites by a third LAL step.…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
“…These were synthesized for the first time by laser ablation technique, using a 248 nm KrF excimer pulsed laser ablation in a solution. (Zhao et al, 2015) Other attempts of coating ZnO were also made, a comprehensive growth mechanism stating a general scheme was developed. (Sun et al, 2013) Polyvinylpyrrolidone (PVP) and 4-mercaptobenzoic acid were crucial in the synthesis of Au/ZnO core/shell nanoparticles.…”
Section: Synthesismentioning
confidence: 99%
“…These materials have good surface plasmon resonance at their interface and the noble metal/semiconductor core/shell composite NS has been one of the most promising composite NSs of the recent decades [4].…”
Section: Introductionmentioning
confidence: 99%